Effect of TiC Particulates on the Microstructure and Mechanical Properties of Aluminium-Based Metal Matrix Composite - Suraya, Sulaiman; Shamsuddin, Sulaiman; Munira, Ali; Fazilah, Adbul Aziz (Trans Tech Publications, Switzerland, 2014)
In this research, metal-matrix composites (MMCs) of aluminium-11.8% silicon alloy matrix reinforced with titanium carbides particulates were fabricated by the casting technique. Aluminium-11.8% silicon alloy is selected as the matrix material and titanium carbide as particulates are mixed in different weight percentages, 5%, 10%, 15% and 20%wt. The cylinder composite castings are made by pouring the composite mixture in copper permanent-molds. The microstructure and mechanical properties of these composite materials were investigated. The effects of reinforced materials on weight percentages addition of particulate on the particulate distribution in aluminium-11.8% silicon alloy composites and SEM observation of the fracture surfaces of tensile tested specimens were deliberate. Moreover, cylinder castings without particulate addition are made and compared with the result based on the properties and microstructural features. It is found that the microstructure and mechanical properties of composites significantly improved by the use of particle reinforced into aluminium alloy.